2005
DOI: 10.1007/978-3-540-30540-8_20
|View full text |Cite
|
Sign up to set email alerts
|

An Upper Bound for the Ramsey Number of a Cycle of Length Four Versus Wheels

Abstract: For given graphs G and H, the Ramsey number R(G, H) is the smallest positive integer n such that every graph F of n vertices satisfies the following property: either F contains G or the complement of F contains H. In this paper, we show that the Ramsey number R(C4, Wm) ≤ m + m 3 + 1 for m ≥ 6.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Tse [25] determined the value of R(C 4 , W n ) for 3 ≤ n ≤ 12. Surahmat et al [23] established an upper bound, which is R(C 4 , W n ) ≤ n + n/3 + 1 for n ≥ 6. Recently, Dybizbański and Dzido [10] refined the upper bound and determined some exact values of R(C 4 , W n ).…”
Section: Theorem 2 (Burr and Erdősmentioning
confidence: 99%
“…Tse [25] determined the value of R(C 4 , W n ) for 3 ≤ n ≤ 12. Surahmat et al [23] established an upper bound, which is R(C 4 , W n ) ≤ n + n/3 + 1 for n ≥ 6. Recently, Dybizbański and Dzido [10] refined the upper bound and determined some exact values of R(C 4 , W n ).…”
Section: Theorem 2 (Burr and Erdősmentioning
confidence: 99%
“…Surahmat et al [8] showed that R(C 4 , W m ) = 9, 10 and 9 for m = 4, 5 and 6 respectively. Independently, Kung-Kuen Tse [10] showed that R(C 4 , W m ) = 10, 9, 10, 9, 11, 12, 13, 14, 16 and 17 for m = 4, 5, 6, 7, 8, 9, 10, 11, 12 and 13, respectively.…”
Section: Every Pair Of Non-adjacent Vertices V and W Of G Then G Is mentioning
confidence: 99%
“…Independently, Kung-Kuen Tse [10] showed that R(C 4 , W m ) = 10, 9, 10, 9, 11, 12, 13, 14, 16 and 17 for m = 4, 5, 6, 7, 8, 9, 10, 11, 12 and 13, respectively. In 2005, Surahmat et al [9] obtained property that R(C 4 , W n ) ≤ n + (n − 1)/3 . Suppose that we have an admissible coloring of K m without C 4 in color 1 and without W n in color 2.…”
Section: Every Pair Of Non-adjacent Vertices V and W Of G Then G Is mentioning
confidence: 99%
“…An interesting question in this respect is: what is the best possible upper bound for R(W n , C 4 )? Surahmat et al [9] showed that R(W n , C 4 ) ≤ n + n/3 + 1 for n ≥ 6. Clearly, this upper bound is not tight in general.…”
Section: Introductionmentioning
confidence: 99%